2020
DOI: 10.26434/chemrxiv.12639215.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Merging Shuttle Reactions and Paired Electrolysis: E-Shuttle Unlocks Reversible Halogenations

Abstract: <p>Polyhalogenated molecules have found widespread applications as flame retardants, pest-control agents, polymers and pharmaceuticals. They also serve as versatile synthetic intermediates in organic chemistry due to the inherent reactivity of carbon-halogen bonds. Despite these attractive features, the preparation of polyhalogenated molecules still mainly relies on the use of highly toxic and corrosive halogenating reagents, such as Cl<sub>2</sub> and Br<sub>2</sub>, which are ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…Importantly, together with the Waldvogel group, Morandi and co-workers showed that dissociative electron transfer pathways can be used to overcome bottlenecks in conventional shuttle catalysis schemes. [25] In constant current electrolysis conditions, 1,2-dichloro species were reductively cleaved to mono-chlorinated radicals, that readily expel chloride after further reduction. Mn(II)-electrocatalysts could then oxidize (at the anode) the alkene co-substrate to the corresponding dichloride in a domino paired electrolysis setup.…”
Section: Recent Applications Of Dissociative Electron Transfer Reactivity In Organic Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, together with the Waldvogel group, Morandi and co-workers showed that dissociative electron transfer pathways can be used to overcome bottlenecks in conventional shuttle catalysis schemes. [25] In constant current electrolysis conditions, 1,2-dichloro species were reductively cleaved to mono-chlorinated radicals, that readily expel chloride after further reduction. Mn(II)-electrocatalysts could then oxidize (at the anode) the alkene co-substrate to the corresponding dichloride in a domino paired electrolysis setup.…”
Section: Recent Applications Of Dissociative Electron Transfer Reactivity In Organic Synthesismentioning
confidence: 99%
“…Development of an e-shuttle catalytic scheme (two functional groups shuttling) to overcome limitations of current (hydro)functionalization shuttle catalysis. [25] These examples highlight the important role that dissociative electron transfer schemes exert in modern organic synthesis. They also show how a detailed mechanistic picture of the elementary steps and rate constants may allow to fine-tune the reactivity and to develop highly selective processes under mild conditions.…”
Section: Recent Applications Of Dissociative Electron Transfer Reactivity In Organic Synthesismentioning
confidence: 99%